The Role of Economic Empowerment of Youth in Reducing Illegal Immigration in Arab Republic of Egypt A Field Study - El Ziadi, Dalia (The Arab Journal of Administration, 2020)
The Researcher made a field study on the role of economic empowerment of youth in reducing the illegal immigration in Arab Republic of Egypt. The research dealt with the following axis: the historical development and economic theories related to illegal immigration, the fact of economic empowerment in Egypt, the fact of illegal immigration in Egypt and its reasons and the methods of controlling illegal immigration in Egypt. A field study was made on individuals who were not able to immigrate illegally. The number of actual sample individuals of youth are (260 individuals). The following descriptive statistical methods are used: The internal coherence coefficient, vaccronbach coefficient, the arithmetic mean and standard deviation. Also the following statistical deductive methods are used: the analysis of unidirectional variance, pearson correlation coefficient, simple regression analysis and multiple regression analysis. The study reached the following results: The existence of moral effect of statistical function between the dimensions of economic empowerment of youth in reducing illegal immigration in Arab Republic of Egypt. There are no core difference between the dimensions of (the economic empowerment of youth in Arab Republic of Egypt) according to their demographic characteristics (sex – age – educational qualification – level of income). The existence of core difference of the dimensions (illegal immigration in Arab Republic of Egypt) according to their demographic characteristics (sex – age – educational qualification – income level).